Efforts to Improve Learning Outcomes in Fiqh Subjects through Advocacy Methods at MTS Al-Huda East Bekasi - Kamil, Yusuf (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
This study aims to improve student learning outcomes in Islamic Jurisprudence learning using the advocacy learning method. The advocacy method is a student-centered learning method that is often identified with the debate process. The research used is classroom action research (CAR) with two cycles. The implementation procedure refers to the model developed by Kurt Lewin where each cycle consists of four components, namely planning, implementation, observation, and reflection. The subjects of the study were 35 students of class VIII-1 MTs Al-Huda Bekasi Timur in the 2014/2015 academic year, consisting of 19 female students and 16 male students. Based on the results of the tests that have been carried out by students, the number of students who achieved the predetermined KKM was 70. In cycle I, 29 students or 85.7% achieved KKM. And learning outcomes in cycle II, 35 students or 100% achieved KKM. Then the average student learning outcomes in cycle I reached 72.9 and in cycle II there was a better increase reaching 82.6. From the results of this study, it can be concluded that the advocacy method can improve the learning outcomes of Islamic jurisprudence for class VIII-1 students at MTs Al-Huda Bekasi